The Impact of Monitoring Mechanism on Efficiency Change and Productivity Growth of Private Commercial Banks in Bangladesh - Naznin Sultana Chaity; S.M. Shafiul Alam (European Scientific Journal, ESJ, 2021)
This paper focuses on understanding the effects of monitoring mechanism (i.e., board quality as well as ownership structure) on efficiency and productivity changes of private commercial banks in Bangladesh over the period from 2007 to 2016. Two non-parametric methods - data envelopment analysis and malmquist productivity index - were used to determine the efficiency and productivity of private commercial banks in Bangladesh. Based on constant returns to scale, five inputs and two outputs have been used to determine the efficiency scores and to identify any improvement in productivity over the period. It was found that private commercial banks of Bangladesh are at the efficiency level of 80.84%. The productivity of all private commercial banks does not follow any trend. Out of twenty two (22) PCBs, only nine (9) banks could manage to increase productivity. Hypothesis test (one sample t-test) are conducted to validate the results. The impact of stock market crisis period on the overall productivity and efficiency of the banks is also evident.